The Impact of Teaching Vocabulary for Junior High School Students Using Scrabble Game - sulaiman, sulaiman (Universitas Nurul Jadid, 2019)
ABSTRACTThis research aimed to investigate the use of teaching vocabulary using Scrabble Game on the students’ achievement. The method applied in this research is Pre-experimental research. Pre-experimental research use three group Pre-test and Post-test. The sample of this research is the first grade students of SMP Negeri 1 sungai Raya Kepulauan.The experimental group was given a pre-test consisted 20 items of test (that was initially tried out before at the same class). After the Pre-test was done, it was continued with three times of treatments where the researcher used 20 words as the screabble material, antonym and synonym words. After the treatments were given, a Post-test with the same test items was administered. The result of Pre-test and Post-test were calculated and compared to determine significant increase by using the matched t-test formula. The research finding the t observed value is 3.66 indicated that the treatments have an effect on performance. Since the value of the observed t value is 3.66 exceeds the t critical value of 2.262 at the intersection of 9 df and .05, it shows that the students’ scores differ significantly from Pre-test to Post-test. This research shows that teaching vocabulary using scrabble game increases the students’ achievement onvocabulary. Scrabble game is basically suggested and considered good and appropriate as technique at teaching vocabulary.Keywords : scrabble game, vocabulary, pre experimental.